MANAGEMENT OF ENDOCRINE DISEASE: Differential diagnosis, investigation and therapy of bilateral adrenal incidentalomas - Isabelle Bourdeau; Nada El Ghorayeb; Nadia Gagnon; André Lacroix (2018)
The investigation and management of unilateral adrenal incidentalomas have been extensively considered in the last decades. While bilateral adrenal incidentalomas represent about 15% of adrenal incidentalomas (AIs), they have been less frequently discussed. The differential diagnosis of bilateral incidentalomas includes metastasis, primary bilateral macronodular adrenal hyperplasia and bilateral cortical adenomas. Less frequent etiologies are bilateral pheochromocytomas, congenital adrenal hyperplasia (CAH), Cushing's disease or ectopic ACTH secretion with secondary bilateral adrenal hyperplasia, primary malignancies, myelolipomas, infections or hemorrhage. The investigation of bilateral incidentalomas includes the same hormonal evaluation to exclude excess hormone secretion as recommended in unilateral AI, but diagnosis of CAH and adrenal insufficiency should also be excluded. This review is focused on the differential diagnosis, investigation and treatment of bilateral AIs.